Відповідь:
[tex]1) 5\frac{3}{14} \\ 2)4\frac{1}{8} \\ 3)7 \frac{7}{36} [/tex]
Обяснение:
[tex]1)8 \frac{9}{14} - 3 \frac{3}{7} = (8 - 3) + ( \frac{9}{14} - \frac{3}{7} ) = 5 + \frac{3}{14} = 5 \frac{3}{14} [/tex]
[tex]2)7 \frac{5}{12} - 3 \frac{7}{24} = (7 - 3) + ( \frac{5}{12} - \frac{7}{24}) = 4 + \frac{1}{8} = 4 \frac{1}{8} [/tex]
[tex] 3)12 \frac{11}{12} - 5 \frac{13}{18} = (12 - 5) + (\frac{11}{12} - \frac{13}{18} ) = 7 + \frac{7}{36} = 7 \frac{7}{36} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
[tex]1) 5\frac{3}{14} \\ 2)4\frac{1}{8} \\ 3)7 \frac{7}{36} [/tex]
Обяснение:
[tex]1)8 \frac{9}{14} - 3 \frac{3}{7} = (8 - 3) + ( \frac{9}{14} - \frac{3}{7} ) = 5 + \frac{3}{14} = 5 \frac{3}{14} [/tex]
[tex]2)7 \frac{5}{12} - 3 \frac{7}{24} = (7 - 3) + ( \frac{5}{12} - \frac{7}{24}) = 4 + \frac{1}{8} = 4 \frac{1}{8} [/tex]
[tex] 3)12 \frac{11}{12} - 5 \frac{13}{18} = (12 - 5) + (\frac{11}{12} - \frac{13}{18} ) = 7 + \frac{7}{36} = 7 \frac{7}{36} [/tex]